Genetic parameter estimates for gastrointestinal nematode parasite resistance and maternal efficiency indicator traits in Santa Ines breed - Berton, Mariana P. [UNESP]; Silva, Rosiane P.; Carvalho, Felipe E.; Justino Chiaia, Hermenegildo Lucas [UNESP]; Oliveira, Priscila S.; Eler, Joanir P.; Banchero, Georgget; Ferraz, Jose B. S.; Baldi, Fernando [UNESP] (Wiley-Blackwell, 2019)
Infection with Haemonchus contortus is the most economically important gastrointestinal nematode parasitosis and the most important cause of mortality in sheep production. The aim of this study was to estimate variance components of gastrointestinal parasite resistance traits, maternal efficiency (ME) and ewe adult weight (AW) in Santa Ines breed in tropical conditions. The phenotypic records were collected from 700 animals, belonging to four flocks located south-east and north-east in Brazil. The evaluated traits were as follows: degree of anaemia assessed using the FAMACHA chart (FMC), haematocrit (HCT), white blood cell (WBC), red blood cell (RBC), haemoglobin (HGB), platelets (PLT), faecal egg count (EPG(log)), ME, metabolic maternal efficiency (MME), AW and metabolic ewe adult weight (MAW). From the 700 animals, 576 (82% of the evaluated population) were genotyped with the Ovine SNP12k BeadChip (Illumina, Inc.). Markers with unknown genomic position, located on sex chromosomes, monomorphic, with minor allele frequency <0.05, call rate <90% and with excess heterozygosity were excluded. The variance components were estimated using a single-trait animal model with ssGBLUP procedure. The correlation between the parasite's resistance indicators and the ME suggested that selecting animals with both higher adult weight and ME will also favour the selection of animals with better resistance to gastrointestinal nematodes parasites, specially H. contortus. Therefore, since there are few or no studies with Santa Ines breed in this area, it is important to study those traits to better manage selection programs.
Keywords: maternal efficiency; parasite resistance; Santa Ines breed